SURFACE STERILIZATION AND CALLUS INDUCTION POTENTIAL OF VARIOUS INDICA RICE (Oryza sativa L.) VARIETIES (Applied Biological Research, 2023)
The present study was conducted to standardize the efficient and reliable  surface sterilization and callus induction protocol for 22 rice (Oryza sativa L.) varieties developed by Dr. Balasaheb Sawant Konkan Krishi  Vidyapeeth, Dapoli, Maharashtra (India) using different combinations of  various plant growth regulators. The dehusked mature rice seed was used  as explant. Prior to callus induction, surface sterilization protocol was  standardized using 70% ethanol and different concentrations of mercuric  chloride (HgCl2). The results revealed that surface sterilization treatment  with 70% ethanol for 1 min, followed by 1.0% HgCl2 for 10 min and then  washing the seeds 4-5 times was most effective in establishing maximum  aseptic cultures (86.67%). Callus induction potential differed significantly  among the rice varieties for the concentrations of plant growth regulators  in MS medium. Rice cv. ‘Ratnagiri-711’ followed by cv. ‘Karjat-8’ were  most superior in callus induction and proliferation potential with the  respective callus induction frequency of 87.56 and 87.0%, and callus weight  of 269.37 and 235.20 mg after 45 days of inoculation. The supplementation  of 2,4-D @ 1.0 to 2.0 mg L-1 along with 0.5 mg L-1 BAP in MS medium was  found optimum for embryogenic callus formation. All the calli formed on  MS medium supplemented with combinations of plant growth regulators  were yellowish-white in colour but with different textures as compact, soft,  friable that were embryogenic and mucilaginous that were non embryogenic.
Keywords: 2,4-D; callus induction protocol; proliferation potential; rice; surface sterilization